A química na odontologia: contribuições para o ensino - Storgatto, Greyce Arrúa (2016)
This research considers the theme "Chemistry in Dentistry" as a starting point for the contextualization of chemical content, in order to contribute to the Chemistry teaching and learning process to 3rd year high school students of a public school in the city of Santa Maria, RS. In dealing with the chemistry involved in common materials of dental practice, as well as in common problems of oral health and aspects of prevention and treatment, Chemistry in Dentistry aims to the Social Chemical Theme "Oral Health", that has already been presented in Chemistry teaching in other works of our research group, LAEQUI. In this research, several interventions were developed, which allowed the structuring of its implementation in three stages: the first corresponds to the presentation of the theme to the students, and the others correspond to the two thematic workshops, guided by Three Pedagogical Moments. The development of these workshops seeks, besides to contextualize chemical content from the theme "Chemistry in Dentistry", to contribute to civic education of students, encouraging them to reflect on their habits regarding oral health and lead them to the perception that chemical knowledge can help to understand the causes of oral health problems, as well as prevention and treatment of these. In the thematic workshops are inserted experimental activities, the didactic game and the case studies as methodological strategies to relate chemical content with the daily life of students from the perspective of the theme, beyond the study of concepts. For data collection, instruments such as questionnaires, exercises, textual production and log books (records notebooks, both the researcher as students) were used and analyzed according to the Discursive Textual Analysis. The results allow us to conclude that the theme Chemistry in Dentistry associated with the use of different teaching methodologies, such as thematic workshops, provided an approximation of Chemistry with the daily life of students, promoting the teaching and learning process of chemical content and their civic education.